The close relationship between heparanase and epithelial mesenchymal transition in gastric signet-ring cell adenocarcinoma - Shah, Shahid (Oncotarget, 2018)
Heparanase (HPSE), a heparan sulfate-specific endo-β-D-glucuronidase, plays an important role in tumor cell metastasis through the degradation of extracellular matrix heparan sulfate proteoglycans. Suramin, a polysulfonated naphthylurea, is an inhibitor of HPSE with suramin analogues. Our objective was to analyze the HPSE involvement in gastric signet ring cell adenocarcinoma (SRCA) invasion. High expression of HPSE mRNA and protein was found in the tumor and in ascites of SRCA as well as in KATO-III cell line. Beside of collagen-I, growth factors (TGF-β1 and VEGF-A, except FGF-2) and epithelial mesenchymal transition (EMT) markers (Snail, Slug, Vimentin, α-SMA and Fibronectin, except E-cadherin) were found higher in main nodules of SRCA as compared to peritumoral sites. Among MDR proteins, MDR-1 and LRP (lung resistance protein) were highly expressed in tumor cells. The formation of 3D cell spheroids was found to be correlated with their origin (adherent or non-adherent KATO-III). After treatment of KATO-III cells with a HPSE inhibitor (suramin), cell proliferation and EMT-related markers, besides collagen-1 expression, were down regulated. In conclusion, in SRCA, HPSE via an autocrine secretion is involved in acquisition of mesenchymal phenotype and tumor cell malignancy. Therefore, HPSE could be an interesting pharmacological target for the treatment of SRCA.